Effects of acute oxygen supplementation on functional capacity and heart rate recovery in Eisenmenger syndrome. (15th March 2017) - Gonzaga, Laion R.A; Matos-Garcia, Bruna C.; Rocco, Isadora S; Begot, Isis; Bolzan, Douglas W; Tatani, Solange B; Santos, Vinicius B; Silva, Célia M.C; Carvalho, Antonio C.C; Arena, Ross; Gomes, Walter J; Guizilini, Solange
Abstract: Background: Eisenmenger syndrome (ES) precipitates the extreme manifestation of pulmonary hypertension, which leads to severe functional limitation and poor quality of life. The propose of the current study was: 1) examined the acute effects of 40% oxygen supplementation during the 6-minute walk test (6MWT); and 2) evaluate the relation between exercise capacity and clinical cardiac parameters in patients with ES. Methods: Thirty subjects were prospectively included; all were submitted to a 6MWT with compressed air and with 40% of oxygen. Heart rate recovery at the first minute (HRR1 ) and perceived effort Borg scale for dyspnea and lower limb fatigue were recorded in both tests scenarios. Results: The 6MWT distance was modestly, negatively associated with pulmonary vascular resistance (PVR) [r = 0.46, p = 0.02]. Patients improved 6MWT distance (p < 0.001) and exhibited a faster HRR1 (p < 0.001) with 40% supplemental oxygen compared to compressed air. With 40% supplemental oxygen, subjects revealed lower dyspnea and lower limb fatigue compared to 6MWT without oxygen supplementation (p < 0.001). The amount of change in the 6MWT distance from air to oxygen was moderate, positively associated with tricuspid annular plane systolic excursion (TAPSE) and right ventricular fractional area change (RVFAC ) [r = 0.50, p = 0.03; r = 0.64, p < 0.001, respectively]. Conclusion: Acute 40% oxygen supplementation in patients with Eisenmenger syndrome led to an improvement in 6MWT distance, faster HRR1 and lower dyspnea and lower limb fatigue perception. Moreover, functional capacity was positively associated with right ventricular parameters.